Brincadeiras sensoriais como ferramentas de aprendizagem no berçário - Barreiros, Angélica Costa (Universidade Federal de São Carlos, 2025)
This article was conceived based on the experience acquired in my professional activity in early childhood education, especially in caring for babies. The work seeks to show how sensory games are a fundamental tool that promotes playfulness and favors the integral development of children. The focus of this research is on babies aged 4 months to 1 year in Nursery I at Creche M.S.M, through a case study using a qualitative approach. The research aims to observe and analyze sensory interactions in the routine of babies, understanding play as a right and pedagogical practice from an early age. Authors such as Emmi Pikler, Elvira Souza Lima, Kishimoto, Gabriela Tabet and Jean Piaget emphasize the importance of sensory, bodily and affective experiences in the construction of children's knowledge. Thus, this work contributes to the appreciation of sensory games in the context of daycare, reaffirming their role in the cognitive, emotional and social development of babies.
Sensory play as learning tools in the nursery
Keywords: Brincadeiras sensoriais; Ludicidade; Bebê; Berçário; Desenvolvimento infantil; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM